Dose-dependent sensitivity of human three-dimensional chromatin to a heart disease–linked transcription factor - Zoe L. Grant; Shuzhen Kuang; Shu Zhang; Abraham J. Horrillo; Zhe Chen; Kavitha S. Rao; Cemre Celen; Vasumathi Kameswaran; Carine Joubran; Pik Ki Lau; Keyi Dong; Bing Yang; et al. (Science, 2026)
Dosage-sensitive transcription factors (TFs) underlie altered gene regulation in human developmental disorders, and cell type–specific gene regulation is linked to the reorganization of three-dimensional (3D) chromatin during cellular differentiation. In this work, we show dose-dependent regulation of chromatin organization by the congenital heart disease (CHD)–linked, lineage-restricted TF TBX5 in human cardiomyocyte differentiation. Genome organization, including compartments, topologically associated domains, and chromatin loops, was sensitive to reduced TBX5 dosage in a human model of CHD, with variations in response across individual cells. Cohesin binding was reduced at TBX5-bound enhancer elements in a TBX5 dose-dependent manner, providing a potential mechanism for disrupted loop formation. These results highlight the importance of lineage-restricted TF dosage in cell type–specific 3D chromatin dynamics, suggesting a mechanism for TF-dependent disease.